The medici return ebook - Berry, Steve (Cotton Malone, 2025)
From celebrated  New York Times  bestselling author Steve Berry comes the latest installment in his wildly popular Cotton Malone series—now in development as a streaming series. The Medici Return takes Cotton to Italy to solve a five hundred year-old mystery.   Cotton Malone is on the hunt for a forgotten 16th century Pledge of Christ—a sworn promise made by Pope Julius II that evidences a monetary debt owed by the Vatican, still valid after five centuries—now worth in the trillions of dollars.  But collecting that debt centers around what happened to the famed Medici of Florence—a family that history says died out, without heirs, centuries ago.  Who will become the next prime minister of Italy, and who will be the next pope? Finding answers proves difficult until Cotton realizes that everything hinges on when, and if, the Medici return.